Asteroid Hyalosis Masquerading as Vitreous Hemorrhage on Point‐of‐Care Sonography. (17th July 2017) - Lema, Penelope C.; Mantuani, Daniel; Nagdev, Arun; Adhikari, Srikar
Abstract : Point‐of‐care ocular sonography is frequently used in the emergency department to evaluate patients with vision disorders. We describe a case series of 3 patients who ultimately had a diagnosis of asteroid hyalosis, a lesser‐known condition that on point‐of‐care sonography may be mistaken for vitreous hemorrhage. Asteroid hyalosis is considered a benign degenerative condition. In contrast, vitreous hemorrhage may be an ocular emergency that warrants an urgent ophthalmologic consultation if there is an underlying retinal tear or detachment. Although similar in appearance on sonography, recognition of the subtle pathognomonic sonographic features along with their clinical presentations can differentiate these diseases, with vastly different management strategies and dispositions.